A kind of iron-nickel-cobalt high temperature alloy and preparation method thereof
By optimizing the composition and preparation process of iron-nickel cobalt high-temperature alloy, a stable microstructure and reinforced phase are formed, which solves the problem of insufficient performance of the alloy in high-temperature environments, and achieves significant improvements in creep, fatigue and oxidation resistance.
Patent Information
- Application Number
- CN202411911143.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing iron-nickel cobalt high-temperature alloys have problems such as uneven component distribution, unstable microstructure, and insufficient fatigue resistance in high-temperature environments, which limit their application in higher temperature and more complex environments.
By optimizing the alloy composition, adding elements such as Cr, Mo, Ti, Re, Hf, Y, Nb, Ge, Ce, etc., and using vacuum induction smelting, electroslag remelting, multi-stage aging treatment and thermal isostatic pressing, the molybdenum-rich phase, Cr-Mo eutectomy phase and stable compounds are formed to improve the creep resistance and high temperature strength of the alloy.
It significantly improves the creep resistance, fatigue resistance and oxidation resistance of the alloy in high temperature environments, enhances the long-lasting strength and stability of the material at high temperatures, and extends the service life of the material.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal materials, and in particular to an iron-nickel-cobalt high-temperature alloy and a preparation method thereof. Background Art
[0002] As the requirements for material properties in high-temperature environments continue to increase, iron-nickel-cobalt superalloys have been widely used in aviation, energy, metallurgy and other fields due to their excellent mechanical properties and high-temperature stability, especially under extreme conditions such as gas turbine engines and high-temperature reactors. Traditional iron-nickel-cobalt superalloys often add elements such as nickel, cobalt, and chromium to improve the strength, oxidation resistance and creep resistance of the alloy. However, as high-temperature use conditions become increasingly harsh, the performance of traditional alloys is still facing challenges, especially the increasing demand for durability, oxidation resistance, corrosion resistance and creep resistance at high temperatures.
[0003] There are still some problems with the existing high-temperature alloy formulas and preparation processes, such as uneven composition distribution, unstable microstructure, and insufficient fatigue resistance, which limit their application in higher temperatures and more complex environments. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention aims to provide an iron-nickel-cobalt high-temperature alloy and a preparation method thereof.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] An iron-nickel-cobalt high-temperature alloy, the components of the high-temperature alloy are as follows in terms of mass percentage:
[0007] Cr: 6%-8%, Mo: 1%-2%, Ti: 1%-2%, Re: 0.5%-1%, Hf: 2.5%-3%, Y: 1%-3%, Nb: 0.3-0.5%; Ge: 0.1~0.2%; Ce: 0.05%-0.1%, Fe: 14%-20%, Co: 10%-15%, Ni: balance, and inevitable impurities such as C and P.
[0008] The main functions of the various elements added to the iron-nickel-cobalt high-temperature alloy are as follows:
[0009] Iron, nickel and cobalt are the main elements of the alloy. Cobalt and iron together with nickel form the matrix structure of the alloy. Nickel (Ni) is the matrix element of the alloy, which provides the toughness and ductility of the material. The introduction of cobalt significantly improves the high temperature strength and reduces creep. At high temperatures, cobalt helps stabilize the crystal structure of the alloy to prevent it from plastic deformation or creep. Iron enhances the overall strength of the matrix while maintaining the toughness and durability of the material. With the combined effect of the two, the alloy shows excellent stability in high temperature environments.
[0010] Specifically, the synergistic effect of nickel and iron together forms a solid matrix structure, provides stable mechanical properties and fatigue resistance, and makes the matrix more stable at high temperatures without affecting the overall ductility and impact resistance. The synergistic effect of nickel and cobalt reduces creep, allowing the material to maintain strength and durability in extremely high temperature environments, significantly improving the high-temperature endurance strength of the material. And with the synergy of cobalt and iron, the creep behavior of the alloy is delayed under high-temperature stress, making it more suitable for long-term work under high-temperature conditions.
[0011] The addition of chromium (Cr) can provide the alloy with good oxidation resistance and corrosion resistance. At high temperatures, chromium can quickly form a dense chromium oxide protective film to prevent the penetration of oxygen and other corrosive media. Molybdenum (Mo) is a solid solution strengthening element. The addition of molybdenum significantly improves the high temperature strength of the alloy. Molybdenum can also prevent excessive growth of grains in high temperature environments, ensuring that the alloy maintains a fine and stable structure at high temperatures for a long time. When chromium and molybdenum are added together, there is a synergistic effect between the two. The synergy of chromium and molybdenum reduces grain boundary sliding, enhances the stability of the alloy at high temperatures, and further enhances the overall corrosion resistance of the alloy, so that the material can maintain chemical stability in extreme environments and prevent premature aging or failure. And through the control of the process in the preparation of the alloy, through multi-stage aging treatment, and through multi-stage precipitation effect, molybdenum-rich phase and Cr-Mo eutectoid phase are formed in the alloy, which further improves the creep resistance and high temperature strength of the material, enhances the stability of the grain boundary and the fatigue resistance of the material, thereby improving the alloy performance at high temperatures.
[0012] Secondly, chromium and cobalt also have a certain synergistic effect. The two together improve the stability of the formed antioxidant layer, and also make the material exhibit good antioxidant and anti-corrosion properties in long-term use.
[0013] The synergistic effect of niobium and germanium in high-temperature alloys can significantly improve the comprehensive properties of the alloy. As an important strengthening element, niobium can form high-temperature stable intermetallic compounds (such as NbC) with carbon. These carbides are distributed in the alloy matrix in the form of fine dispersed particles, effectively hindering dislocation movement and enhancing the high-temperature strength and creep properties of the alloy. At the same time, the addition of niobium can also promote the stability of certain strengthening phases (such as γ′ phase or γ″ phase), making it have longer thermal stability at high temperatures and significantly delaying the performance degradation of the alloy.
[0014] The role of germanium in high-temperature alloys is mainly reflected in two aspects: oxidation resistance and toughness enhancement. In high-temperature environments, germanium works synergistically with traditional antioxidant elements (such as chromium and nickel) to promote the compactness and stability of the oxide film, thereby improving the durability of the alloy in oxidation and sulfidation environments. In addition, the presence of germanium can enhance the strength of the metal bond by optimizing the electronic structure of the alloy, thereby improving the overall toughness of the alloy and reducing the risk of crack propagation during high-temperature operation. At the same time, the addition of germanium may affect the distribution and morphology of the γ′ phase, further optimizing the microstructure of the alloy.
[0015] The synergistic effect of niobium and germanium is also reflected in their joint participation in strengthening the matrix and interface bonding. Niobium carbides enhance the matrix strength, while germanium electronic structure adjustment improves the alloy's plastic deformation ability. The combination of the two can achieve a better balance between high-temperature creep and fatigue resistance. This balance is particularly important for alloys used in extreme high-temperature environments (such as turbine blade materials). Titanium (Ti) is an important precipitation element for strengthening alloys. Titanium can form γ' phase (Ni3Ti), provide precipitation hardening effect at high temperature, improve creep resistance and high-temperature strength. In addition, titanium improves the hardness and stability of the alloy through the formation of precipitation phases. The addition of hafnium (Hf) is intended to strengthen grain boundaries and improve the creep resistance and high-temperature toughness of the material. Hafnium can form stable compounds at grain boundaries to prevent grain boundary sliding, delay creep and crack propagation. Hafnium can also improve the bonding force at the grain boundary and reduce the initiation and propagation of cracks.
[0016] When titanium and hafnium are added to the alloy together, the introduction of hafnium can stabilize and refine the γ' phase (Ni3Ti) formed by titanium, making it more stable at high temperatures. This helps to delay the coarsening and failure of the phase, thereby extending the service life and high-temperature performance of the material. Secondly, hafnium forms stable compounds at the grain boundaries, enhancing the grain boundary bonding force, preventing grain boundary sliding, and reducing creep and crack propagation. This grain boundary strengthening effect can complement the precipitation strengthening mechanism formed by titanium to improve the high-temperature creep resistance of the overall alloy.
[0017] Trace amounts of carbon will precipitate with hafnium during the smelting process of the alloy to form hafnium carbide. As a strong carbide, hafnium carbide (HfC) maintains the fine structure of the grains at high temperatures, provides excellent grain boundary strengthening effects, prevents grain growth and structural deformation, and thus can enhance the stability and oxidation resistance of the alloy at ultra-high temperatures without significantly increasing the brittleness of the material. Yttrium oxide can promote the stability of the alloy grain boundaries at higher temperatures, and delay the creep and fatigue failure of the alloy by inhibiting the slip and dislocation climb of the grain boundaries. While hafnium carbide enhances the oxidation resistance at higher temperatures, combined with the grain boundary stabilization effect of yttrium oxide, the stability of the alloy in ultra-high temperature and high stress environments is further improved.
[0018] During the smelting process of the alloy, the yttrium element will absorb a small amount of oxygen in the melt, so that part of the yttrium element will be transformed and precipitated into yttrium oxide during the smelting process of the alloy. The yttrium oxide particles play a pinning role at the grain boundary, inhibiting grain boundary sliding and significantly improving the high-temperature creep performance of the alloy. The yttrium content needs to be controlled within the range of 1%-3%. Too low will limit the amount of yttrium oxide generated, and too high may cause particle aggregation or coarsening.
[0019] The combined effects of yttrium oxide, hafnium carbide, hafnium and titanium further enhance the stability of the material in high temperature environments, reduce performance degradation caused by oxidation, and further enhance the creep resistance of the material in high temperature stress environments, ensuring the long life and durability of the material.
[0020] Rhenium (Re) is an extremely important solid solution strengthening element. Although its content is low, its effect on improving the high temperature performance of the alloy is also very significant. Rhenium has a high melting point and can inhibit grain boundary sliding, thereby preventing the alloy from deformation and creep at high temperatures. Rhenium improves the stability of the grain boundaries through solid solution strengthening, which enables the alloy to maintain good mechanical properties at extreme temperatures. Secondly, rhenium and hafnium have a synergistic effect, and they jointly strengthen the stability and high temperature strength of the grain boundaries: rhenium inhibits grain boundary movement, while hafnium increases the bonding strength of the grain boundaries, thereby further delaying high temperature creep behavior.
[0021] The present invention also adds the rare earth element cerium (Ce). Although the amount of cerium (Ce) added is small, it plays an important role in inhibiting impurity elements and improving the oxidation resistance of the alloy. Cerium can combine with impurity elements such as oxygen and sulfur to reduce their negative impact on the performance of the alloy. Secondly, the rare earth element cerium can also form a dense protective film on the surface and grain boundaries of the alloy, which works together with the stable compounds formed by hafnium and rhenium to help improve the material's oxidation resistance and corrosion resistance. Secondly, the combination of titanium and the rare earth element cerium also further enhances the overall stability of the alloy: the precipitation strengthening effect of titanium becomes more durable under the action of the rare earth element cerium, and the rare earth element cerium improves the stability of the precipitated phase and enhances the oxidation resistance.
[0022] Therefore, the present invention can achieve comprehensive high-temperature strengthening by adjusting the distribution of rhenium and hafnium in the nanostructure and adding titanium and the rare earth element cerium.
[0023] Furthermore, the content of niobium in the high-temperature alloy is in the range of 0.4%-0.45%.
[0024] Furthermore, the content of chromium in the high-temperature alloy is in the range of 6.7%-7.3%.
[0025] Furthermore, the content of molybdenum in the high-temperature alloy is in the range of 1.2%-1.8%.
[0026] Furthermore, the content of titanium in the high-temperature alloy is in the range of 1.3%-1.7%.
[0027] Furthermore, the content of rhenium in the high-temperature alloy is in the range of 0.7%-0.8%.
[0028] Furthermore, the content of hafnium in the high-temperature alloy is in the range of 2.6%-2.7%.
[0029] Furthermore, the content of germanium in the high-temperature alloy is in the range of 0.1%-0.16%.
[0030] Furthermore, the yttrium content in the high-temperature alloy ranges from 1.7% to 2.3%.
[0031] A method for preparing the above-mentioned iron-nickel-cobalt high-temperature alloy comprises the following steps:
[0032] S1: Vacuum induction melting: the raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600-1650°C, the melt temperature is kept stable, and the melting time is 2-3 hours; wherein the nickel and iron raw materials are particles with porous structures;
[0033] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2-3A / cm², the melting temperature is set at 1500-1550℃, and the remelting process lasts 3-4 hours;
[0034] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 6-8h, then switch to 1℃ / min until the temperature drops to room temperature;
[0035] S4: Heat treatment process:
[0036] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0037] (2) Multi-stage aging treatment:
[0038] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0039] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0040] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0041] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0042] Step S1 ensures the uniformity of the alloy composition, reduces inclusions and pores, and improves the purity and initial structural properties of the alloy. Step S2 electroslag remelting further refines the alloy, removes harmful impurities, improves the uniformity and density of the organization, and helps to obtain a refined grain structure, thereby enhancing the mechanical properties of the alloy. Step S3 slow cooling process helps to reduce the formation of thermal stress and internal stress, thereby preventing cracks and internal defects in the ingot. The solution treatment in step S4 ensures the stability of the solid solution structure of the alloy, eliminates the coarse precipitation phase in the cast structure, and increases the machinability and deformation resistance of the material.
[0043] In step S1, the nickel and iron raw materials are particles with a porous structure, so that the nickel and iron raw materials themselves absorb a trace amount of oxygen, so that during the smelting process of the alloy, the yttrium element can combine with oxygen to form yttrium oxide.
[0044] The faster cooling rate (2℃ / min) in the early stage of step S3 can effectively promote rapid nucleation of grains, avoid the formation of coarse grains, and improve the effect of grain refinement. The slower cooling rate (1℃ / min) in the later stage can reduce the accumulation of thermal stress during grain growth and ensure the uniformity of grain size. Staged cooling helps to control the precipitation behavior of carbides (such as NbC) and other strengthening phases (such as γ′ phase). Rapid cooling in the early stage can dissolve part of the solute elements, and slow cooling in the later stage can promote the uniform distribution of precipitated particles. Staged cooling can optimize the dislocation structure and phase distribution in the organization, thereby showing better creep resistance and thermal stability in high temperature environment.
[0045] The first aging stage promotes the formation of fine precipitation strengthening phases, such as the initial precipitation of molybdenum-rich phases, which significantly improves the creep resistance and high-temperature strength of the material. The second aging stage helps the further precipitation of the Cr-Mo eutectoid phase, enhances the stability of the grain boundaries and the fatigue resistance of the material. The third aging stage promotes the further refinement and uniform distribution of the molybdenum-rich strengthening zone, optimizes the overall performance of the alloy, and ensures the stability of the material in high-temperature environments and long-term reliability.
[0046] Step S5 significantly improves the toughness and durability of the material by eliminating micropores and grain boundary defects.
[0047] The multi-stage aging treatment not only strengthens the precipitation effect of molybdenum and chromium in the alloy matrix, but also strengthens the HfC formed by the combination of hafnium and carbon and the Yttrium formed by the combination of yttrium and oxygen. 2 O 3The effect of HfC is significantly affected. HfC has a high melting point and chemical stability in high temperature environments, which enables the alloy to maintain stability and oxidation resistance under ultra-high temperature conditions. Through multi-stage aging, HfC is further evenly distributed in the matrix structure, and this distribution method reduces its potential negative impact on the brittleness of the material. By controlling the aging temperature and time, HfC particles can form a stable and fine distribution in the matrix, which correspondingly improves the overall strength of the alloy.
[0048] Y 2 O 3 As a grain refiner and dislocation movement inhibitor, it also plays a unique role in multi-stage aging treatment. 2 O 3 It can promote the stability of alloy grain boundaries at higher temperatures, and delay the creep and fatigue failure of alloys by inhibiting the slip and dislocation climb of grain boundaries. Multi-stage aging treatment can also promote Y 2 O 3 The particles form eutectic or interface interactions with the strengthening phases precipitated from molybdenum and chromium, further enhancing the high-temperature mechanical properties of the matrix.
[0049] From the perspective of synergy, HfC and Y 2 O 3 The presence of HfC can enhance the multiphase strengthening effect of the alloy in the multi-stage aging treatment. 2 O 3 Combined with the grain boundary stabilization effect, the stability of the alloy in ultra-high temperature and high stress environments is further improved. 2 O 3 The dislocation suppression effect of the alloy can also interact with the precipitation of molybdenum and chromium to reduce dislocation accumulation and deformation instability, and improve fatigue resistance. The synergistic effect of the two in multi-stage aging treatment enables the alloy to have excellent comprehensive mechanical properties and thermal stability in long-term high-temperature service.
[0050] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects:
[0051] The iron-nickel-cobalt high-temperature alloy and its preparation method provided by the present invention achieve significant performance improvement by optimizing the alloy composition and preparation process. The high-temperature alloy exhibits excellent creep resistance, fatigue resistance and oxidation resistance in a high-temperature environment through reasonable element ratio and multi-stage heat treatment. The synergistic effect of elements such as nickel, cobalt, and chromium in the alloy not only enhances the high-temperature strength of the material, but also effectively improves its oxidation resistance and corrosion resistance, so that the alloy has better stability and long life at extremely high temperatures.
[0052] Through the refining process of vacuum induction melting and electroslag remelting, the alloy composition is evenly distributed, impurities and pores are effectively removed, the purity and density are improved, and the mechanical properties of the material are enhanced. The multi-stage aging treatment effectively promotes the precipitation of elements such as molybdenum, chromium, titanium, and rhenium in the alloy, forming a strengthening phase, and improving the creep resistance and high-temperature strength of the material. In particular, the synergistic effect of titanium and hafnium enhances the crack resistance and grain boundary stability of the alloy, allowing it to maintain good mechanical properties at high temperatures.
[0053] In addition, the precipitation of hafnium carbide and yttrium oxide further enhances the high temperature performance of the alloy by refining grains and stabilizing grain boundaries, inhibiting grain growth and thermal stress generation, and reducing deformation and crack propagation of materials at high temperatures. Hafnium carbide provides excellent hardness and wear resistance, while yttrium oxide acts as a grain refiner, effectively improving the alloy's creep resistance and oxidation resistance.
[0054] During the multi-stage aging treatment, the alloy finely controls the temperature and time to make the strengthening phase evenly distributed, thereby improving the comprehensive performance of the alloy at high temperatures. In practical applications, the iron-nickel-cobalt high-temperature alloy can work stably for a long time in high-temperature, oxidizing, and corrosive environments, and has broad application prospects, especially in the fields of aviation, energy, and high-temperature industries. DETAILED DESCRIPTION
[0055] The present invention is described in detail below in conjunction with embodiments.
[0056] Example 1
[0057] This embodiment discloses an iron-nickel-cobalt high-temperature alloy and a preparation method thereof, wherein the chemical composition of the iron-nickel-cobalt high-temperature alloy is as follows in terms of mass percentage:
[0058] Cr: 6%, Mo: 1%, Ti: 1%, Re: 0.5%, Hf: 2.5%, Y: 1%, Nb: 0.3%, Ge: 0.1%, Ce: 0.05%, Fe: 14%, Co: 10%, Ni: balance, and inevitable impurities such as C and P. and inevitable impurities such as C and P.
[0059] The preparation method of the iron-nickel-cobalt high-temperature alloy comprises the following steps:
[0060] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0061] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0062] S3: Ingot cooling: adopt staged cooling method, first control at 2℃ / min cooling for 6h, then switch to 1℃ / min until the temperature drops to room temperature;
[0063] S4: Heat treatment process:
[0064] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0065] (2) Multi-stage aging treatment:
[0066] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0067] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0068] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0069] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0070] Example 2
[0071] This embodiment discloses an iron-nickel-cobalt high-temperature alloy and a preparation method thereof, wherein the chemical composition of the iron-nickel-cobalt high-temperature alloy is as follows in terms of mass percentage:
[0072] Cr: 8%, Mo: 2%, Ti: 2%, Re: 1%, Hf: 2.7%, Y: 3%, Nb: 0.5%, Ge: 0.2%, Ce: 0.1%, Fe: 20%, Co: 15%, Ni: balance, and inevitable impurities such as C and P.
[0073] The preparation method of the iron-nickel-cobalt high-temperature alloy comprises the following steps:
[0074] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0075] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0076] S3: Ingot cooling: adopt staged cooling method, first control at 2℃ / min cooling for 8h, then switch to 1℃ / min until the temperature drops to room temperature;
[0077] S4: Heat treatment process:
[0078] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0079] (2) Multi-stage aging treatment:
[0080] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0081] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0082] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0083] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0084] Example 3
[0085] This embodiment discloses an iron-nickel-cobalt high-temperature alloy and a preparation method thereof, wherein the chemical composition of the iron-nickel-cobalt high-temperature alloy is as follows in terms of mass percentage:
[0086] Cr: 7%, Mo: 1.5%, Ti: 1.5%, Re: 0.75%, Hf: 3%, Y: 2.1%, Nb: 0.4%, Ge: 0.15%, Ce: 0.07%, Fe: 17%, Co: 12%, Ni: balance, and inevitable impurities such as C and P.
[0087] The preparation method of the iron-nickel-cobalt high-temperature alloy comprises the following steps:
[0088] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0089] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0090] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 7h, then switch to 1℃ / min until the temperature drops to room temperature;
[0091] S4: Heat treatment process:
[0092] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0093] (2) Multi-stage aging treatment:
[0094] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0095] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0096] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0097] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0098] Comparative Example 1
[0099] Comparative Example 1 discloses an alloy and a preparation method thereof, wherein the chemical composition of the alloy is as follows in terms of mass percentage:
[0100] Cr: 6%, Mo: 1%, Ti: 1%, Hf: 2.5%, Fe: 14%, Co: 10%, Ni: balance, and inevitable impurities such as C and P.
[0101] The preparation method of the alloy comprises the following steps:
[0102] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0103] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0104] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 7h, then switch to 1℃ / min until the temperature drops to room temperature;
[0105] S4: Heat treatment process:
[0106] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0107] (2) Multi-stage aging treatment:
[0108] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0109] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0110] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0111] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0112] Comparative Example 2
[0113] Comparative Example 2 discloses an alloy and a preparation method thereof, wherein the chemical composition of the alloy is as follows in terms of mass percentage:
[0114] Cr: 6%, Mo: 1%, Ti: 1%, Re: 0.5%, Nb: 0.3%, Ge: 0.1%, Fe: 14%, Co: 10%, Ni: balance, and inevitable impurities such as C and P.
[0115] The preparation method of the alloy comprises the following steps:
[0116] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0117] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0118] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 7h, then switch to 1℃ / min until the temperature drops to room temperature;
[0119] S4: Heat treatment process:
[0120] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0121] (2) Multi-stage aging treatment:
[0122] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0123] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0124] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0125] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0126] Comparative Example 3
[0127] Comparative Example 3 discloses an alloy and a preparation method thereof, wherein the chemical composition of the alloy is as follows in terms of mass percentage:
[0128] Cr: 6%, Mo: 1%, Re: 0.5%, Hf: 2.5%, Fe: 14%, Co: 10%, Ni: balance, and inevitable impurities such as C and P.
[0129] The preparation method of the alloy comprises the following steps:
[0130] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0131] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0132] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 7h, then switch to 1℃ / min until the temperature drops to room temperature;
[0133] S4: Heat treatment process:
[0134] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0135] (2) Multi-stage aging treatment:
[0136] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0137] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0138] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0139] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0140] Comparative Example 4
[0141] Comparative Example 4 discloses an alloy and a preparation method thereof, wherein the chemical composition of the alloy is as follows in terms of mass percentage:
[0142] Cr: 6%, Mo: 1%, Re: 0.5%, Hf: 2.5%, Ce: 0.05%, Fe: 14%, Co: 10%, Ni: balance, and inevitable impurities such as C and P.
[0143] The preparation method of the alloy comprises the following steps:
[0144] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0145] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0146] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 7h, then switch to 1℃ / min until the temperature drops to room temperature;
[0147] S4: Heat treatment process:
[0148] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0149] (2) Multi-stage aging treatment:
[0150] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0151] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0152] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0153] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0154] Comparative Example 5
[0155] Comparative Example 5 discloses an alloy and a preparation method thereof, wherein the chemical composition of the alloy is as follows in terms of mass percentage:
[0156] Cr: 6%, Mo: 1%, Ti: 1%, Ce: 0.05%, Fe: 14%, Co: 10%, Ni: balance, and inevitable impurities such as C and P.
[0157] The preparation method of the alloy comprises the following steps:
[0158] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0159] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0160] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 7h, then switch to 1℃ / min until the temperature drops to room temperature;
[0161] S4: Heat treatment process:
[0162] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0163] (2) Multi-stage aging treatment:
[0164] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0165] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0166] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0167] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0168] Comparative Example 6
[0169] Comparative Example 6 discloses an alloy and a preparation method thereof, wherein the chemical composition of the alloy is as follows in terms of mass percentage:
[0170] Cr: 6%, Mo: 1%, Ti: 1%, Re: 0.5%, Hf: 2.5%, Ce: 0.05%, Fe: 14%, Co: 10%, Ni: balance, and inevitable impurities such as C and P.
[0171] The preparation method of the alloy comprises the following steps:
[0172] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0173] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0174] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 7h, then switch to 1℃ / min until the temperature drops to room temperature;
[0175] S4: Heat treatment process:
[0176] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0177] (2) Multi-stage aging treatment:
[0178] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0179] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0180] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0181] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0182] Comparative Example 7
[0183] Comparative Example 7 discloses an alloy and a preparation method thereof, wherein the chemical composition of the alloy is as follows in terms of mass percentage:
[0184] Cr: 6%, Mo: 1%, Ti: 1%, Hf: 2.5%, Nb: 0.3%, Ge: 0.1%; Y: 1%, Fe: 14%, Co: 10%, Ni: balance, and inevitable impurities such as C and P.
[0185] The preparation method of the alloy comprises the following steps:
[0186] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0187] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0188] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 7h, then switch to 1℃ / min until the temperature drops to room temperature;
[0189] S4: Heat treatment process:
[0190] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0191] (2) Multi-stage aging treatment:
[0192] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0193] Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h;
[0194] Third aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0195] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0196] Comparative Example 8
[0197] This comparative example 8 discloses an alloy and a preparation method thereof, wherein the chemical composition of the alloy is as follows in terms of mass percentage:
[0198] Cr: 6%, Mo: 1%, Ti: 1%, Re: 0.5%, Hf: 2.5%, Y: 1%, Nb: 0.3%; Ge: 0.1%; Ce: 0.05%, Fe: 14%, Co: 10%, Ni: balance, and inevitable impurities such as C and P.
[0199] The preparation method of the iron-nickel-cobalt high-temperature alloy comprises the following steps:
[0200] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0201] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0202] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 7h, then switch to 1℃ / min until the temperature drops to room temperature;
[0203] S4: Heat treatment process:
[0204] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0205] (2) Secondary aging treatment:
[0206] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0207] Secondary aging: heat the material to 650℃ again and keep it warm for 8 hours;
[0208] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0209] Comparative Example 9
[0210] This comparative example 9 discloses an alloy and a preparation method thereof, wherein the chemical composition of the alloy is as follows in terms of mass percentage:
[0211] Cr: 6%, Mo: 1%, Ti: 1%, Re: 0.5%, Hf: 2.5%, Y: 1%, Nb: 0.3%; Ge: 0.1%; Ce: 0.05%, Fe: 14%, Co: 10%, Ni: balance, and inevitable impurities such as C and P.
[0212] The preparation method of the iron-nickel-cobalt high-temperature alloy comprises the following steps:
[0213] S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600°C, the melt temperature is kept stable, and the melting time is 2 hours;
[0214] S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2A / cm², the melting temperature is set to 1500℃, and the remelting process lasts for 3 hours;
[0215] S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 7h, then switch to 1℃ / min until the temperature drops to room temperature;
[0216] S4: Heat treatment process:
[0217] (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching;
[0218] (2) One-time aging treatment:
[0219] Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling;
[0220] S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
[0221] Detection Methods
[0222] 1. According to HB5258-2000, the static oxidation behavior of the samples at 800°C was tested. The oxidation of the samples was detected by weight gain method. Three parallel samples were taken from each group of samples and the average value was calculated as the average oxidation weight gain rate.
[0223] (g·m -2 ·h -1 ), the final test results are shown in Table 1.
[0224]
[0225] 2. The high temperature tensile properties of the samples were tested after being kept at 800°C for 24 hours in accordance with GB / T4338-2006. Three parallel samples were taken from each group of samples and their average values were calculated. The final test results are shown in Table 2.
[0226]
[0227] Among them, R m is the tensile strength, R e is the yield strength, A is the elongation, and Z is the area reduction.
[0228] It can be seen from the above test results that the oxidation weight gain rate of the alloy of the present invention under high temperature conditions is significantly reduced, indicating that its ability to resist high temperature oxidation is significantly improved. Secondly, the tensile strength and yield strength at high temperature are improved to a certain extent. According to the data of elongation and cross-sectional shrinkage, it can be seen that the creep resistance and high temperature stability of the alloy are greatly improved.
[0229] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. An iron-nickel-cobalt high-temperature alloy, characterized in that: The composition of the high temperature alloy is as follows in terms of mass percentage: Cr: 6%-8%, Mo: 1%-2%, Ti: 1%-2%, Re: 0.5%-1%, Hf: 2.5%-3%, Y: 1%-3%, Nb: 0.3-0.5%; Ge: 0.1~0.2%; Ce: 0.05%-0.1%, Fe: 14%-20%, Co: 10%-15%, Ni: balance, and inevitable C and P impurities.
2. The iron-nickel-cobalt high-temperature alloy according to claim 1, characterized in that: The content of niobium in the high-temperature alloy is in the range of 0.4%-0.45%.
3. The iron-nickel-cobalt high-temperature alloy according to claim 1, characterized in that: The content of chromium in the high-temperature alloy is in the range of 6.7%-7.3%.
4. The iron-nickel-cobalt high-temperature alloy according to claim 1, characterized in that: The content of molybdenum in the high-temperature alloy is in the range of 1.2%-1.8%.
5. The iron-nickel-cobalt high-temperature alloy according to claim 1, characterized in that: The content of titanium in the high-temperature alloy is in the range of 1.3%-1.7%.
6. The iron-nickel-cobalt high-temperature alloy according to claim 1, characterized in that: The content of rhenium in the high-temperature alloy is in the range of 0.7%-0.8%.
7. The iron-nickel-cobalt high-temperature alloy according to claim 1, characterized in that: The content of hafnium in the high-temperature alloy is in the range of 2.6%-2.7%.
8. The iron-nickel-cobalt high-temperature alloy according to claim 1, characterized in that: The content of germanium in the high-temperature alloy is in the range of 0.1%-0.16%.
9. The iron-nickel-cobalt high-temperature alloy according to claim 3, characterized in that: The yttrium content in the high temperature alloy is in the range of 1.7% to 2.3%.
10. A method for preparing an iron-nickel-cobalt high-temperature alloy according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Vacuum induction melting: The raw materials are melted under vacuum conditions, the melting temperature is controlled at 1600-1650℃, the melt temperature is kept stable, and the melting time is 2-3 hours; the nickel and iron raw materials are particles with porous structures; S2: Electroslag remelting: Using electroslag remelting technology, the current density is controlled at 2-3A / cm², the melting temperature is set at 1500-1550℃, and the remelting process lasts 3-4 hours; S3: Ingot cooling: adopt staged cooling method, first control cooling at 2℃ / min for 6-8h, then switch to 1℃ / min until the temperature drops to room temperature; S4: Heat treatment process: (1) Solution treatment: heating to 1150°C, keeping temperature for 2 hours, and then water quenching; (2) Multi-stage aging treatment: Primary aging: heating to 750℃, keeping warm for 16 hours, slowly cooling to 500℃ at 10℃ / h, and then air cooling; Secondary aging: heat the material to 700℃ again, keep it for 10 hours, then slowly cool it to 600℃ at a rate of 10℃ / h, keep it for 4 hours, and then continue to slowly cool it to 500℃ at a rate of 10℃ / h; Third aging: heat the material to 650℃ again and keep it warm for 8 hours; S5: Hot isostatic pressing: the temperature is controlled at 1200°C, the pressure is controlled at 100MPa, the isostatic pressing time is controlled at 3 hours, and the cooling method is to slowly cool to 500°C with the furnace and then cool with air.
Citation Information
Patent Citations
Al-Fe-Re-RE aluminum alloy, and preparation method and power cable thereof
CN102978476A
Ni-Co-Al-Cr-Fe series single crystal high-entropy high-temperature alloy and preparation method thereof
CN110317990A